Sun Trailing Solar Panel System for Improving Energy Efficiency - Roy, Pronoy; Das, Ankit; Simlai, Argha; Mondol, Indranil; Nag, Tirthajyoti; Sarkar, Paramita; Ghosh, Jayasree; Bhowmik, Sonali; Bhowmik, Abhishek; Majumdar, Soumya (International Journal of Computer Sciences and Engineering, 2026)
This study delves further into the design and analysis of an Automatic Sun Tracking Solar Panel based on the open loop concept. The primary goal of this project is to maximise solar energy utilisation by effectively capturing sunlight and converting it into electrical energy for a variety of purposes. The method increases power output by putting the solar panel perpendicular to the sun's rays, which maximises sunlight absorption. Moreover, this tracking system operates independently of the intensity of the sunrays, accurately determining the sun's coordinates and automatically adjusting its position accordingly. This method ensures the solar panel's excellent efficiency and dependability. This project's main advantage is its capacity to provide access to a sustainable and ecologically favourable source of energy. This solar tracking system can be integrated into local communities and, when connected to large-scale battery banks, can cater to their energy requirements independently. Overall, this research advances renewable energy technologies, allowing for the broad deployment of solar power systems